2009
DOI: 10.1016/j.mechmat.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Study of the yielding of sand under generalized stress conditions using a versatile hollow cylinder torsional apparatus

Abstract: Please cite this article as: O'Kelly, B.C., Naughton, P.J., Study of the yielding of sand under generalized stress conditions using a versatile hollow cylinder torsional apparatus, Mechanics of Materials (2008Materials ( ), doi: 10.1016Materials ( / j.mechmat.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This may be done in directional shear or in torsion shear equipment with different pressures applied inside and outside the hollow cylinder specimen. Limited and sporadic experimental results have been provided in this respect by Arthur and Menzies (1972), Arthur and Phillips (1975), Hight et al (1983), Miura et al (1986), Pradel et al (1990), O'Kelly (2007), O'Kelly andNaughton (2009) and by Chairo et al (2013). While these studies indicated some variation in the friction angle, none provided a complete picture.…”
Section: Previous Studies Of Cross-anisotropymentioning
confidence: 99%
“…This may be done in directional shear or in torsion shear equipment with different pressures applied inside and outside the hollow cylinder specimen. Limited and sporadic experimental results have been provided in this respect by Arthur and Menzies (1972), Arthur and Phillips (1975), Hight et al (1983), Miura et al (1986), Pradel et al (1990), O'Kelly (2007), O'Kelly andNaughton (2009) and by Chairo et al (2013). While these studies indicated some variation in the friction angle, none provided a complete picture.…”
Section: Previous Studies Of Cross-anisotropymentioning
confidence: 99%
“…Hollow cylinder torsional shear tests have been extensively used in the investigation of inherent and stress-induced anisotropy of soil (e.g., [10][11][12][13][14][15][16]). Using a hollow cylinder torsional apparatus to study the liquefaction characteristics of sand is also found in previous studies (e. g., [17][18][19][20][21][22][23]).…”
Section: Introductionmentioning
confidence: 99%